Modern South Asia : history, culture, political economy - Bose, Sugata, 1956-; Jalal, Ayesha (London ; New York : Routledge Taylor & Francis Group, 1994)
"Provides challenging insights into the history, culture, politics and economics of South Asia over the past three centuries"--Provided by publisher.
South Asian history : an introduction -- Modernity and antiquity : interpretations of ancient India -- Pre-modern accommodations of difference : the making of Indo-Islamic cultures -- The Mughal Empire : state, economy and society -- India between empires : decline or decentralization? -- The transition to colonialism : resistance and collaboration -- The first century of British rule, 1757 to 1857 : state and economy -- Company Raj and Indian society, 1757 to 1857 : re-invention and reform of tradition -- 1857 : rebellion, collaboration and the transition to Crown Raj -- High noon of colonialism, 1858 to 1914 : state and political economy -- A nation in making? : "rational" reform, "religious" revival and Swadeshi nationalism, 1858 to 1914 -- Colonialism under siege : state and political economy after World War I -- Gandhian nationalism and mass politics in the 1920s -- The Depression decade : society, economics and politics -- Nationalism and colonialism during World War II and its aftermath : economic crisis and political confrontation -- The partition of India and the creation of Pakistan -- 1947 : memories and meanings -- Post-colonial South Asia : state and economy, society and politics, 1947 to 1971 -- Post-colonial South Asia : state and economy, society and politics, 1971 to 2017 -- Decolonizing South Asian history : a view from the new millennium -- Glossary -- A chronological outline.
Includes bibliographical references (pages 236-269) and index.
RS, GenEd
Keywords: History; South Asia -- History